Cyberspace Sebagai Area Perang Antara Fans Versus Haters K-Pop di Instagram - kusnul Fitria (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
This research focuses on the fanwar phenomenon that occurs between fans versus haters on Instagram. By using the netnographic method, researchers did non-participatory observations on the accounts of haters and fans on Instagram. The object of this research is Once as a fan group and Thrice as a hate group. The results of the study show that the fan war that occurs on Instagram has several forms, such as fan war through the comments column, through indirect messages and uploads via Instagram stories. During the war process, fans and haters always use harsh, aggressive and disrespectful words or better known as flaming. hassle and block are two events used by fans and haters to avoid fanwar. As fans, fans take the fight to the haters group by creating a counter account to fight the haters account on Instagram. With this resistance aimed at fans not making haters stay silent, haters then create a rival Instagram account to fight the anti-haters account created by these fans.